Análise do potencial técnico do aproveitamento energético ou biotecnológico de resíduos de indústrias citrícolas de pequeno porte - Piancatelli, Felipe [UNESP] (2024)
This dissertation analyzes the technical and economic feasibility of implementing a biorefinery for the processing of citrus waste, focusing on the production of bioethanol, biogas and d-limonene. Initially, the study maps the main solid and liquid waste generated in the production process of concentrated orange juice (FCOJ) and derivatives, highlighting the significant volume of waste generated, such as peels, pulp and liquid extracts, which correspond to approximately 50% of the total mass of the fruit. Based on a detailed analysis of the industrial processes, including extraction, pressing and concentration, different scenarios for the energy and biotechnological use of the waste were evaluated. The study applied financial modeling methodologies and economic feasibility indicators, such as Net Present Value (NPV), Internal Rate of Return (IRR) and payback, comparing the feasibility of an integrated plant for the production of the three aforementioned bioproducts and alternatives for independent production. The results indicated that the biorefinery, in its original configuration, faces substantial economic challenges due to the high initial investment and operational costs required. However, the isolated production of d-limonene proved to be economically viable, offering a promising return, especially in specialized markets. The production of bioethanol and biogas, although environmentally sustainable, is more dependent on tax incentives and policies supporting the circular economy to become financially attractive. In addition to contributing to the reduction of the environmental impacts of the citrus industry, this work proposes solutions that enhance the use of waste, generating new revenue streams and minimizing waste. The sensitivity analysis of the financial scenarios identified that the critical variables affecting the viability of the project are input costs and fluctuations in the commodity market.